2020
DOI: 10.3389/fphar.2020.01276
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-Related Voltage-Gated Sodium Channelopathies: A Review

Abstract: Epilepsy is a disease characterized by abnormal brain activity and a predisposition to generate epileptic seizures, leading to neurobiological, cognitive, psychological, social, and economic impacts for the patient. There are several known causes for epilepsy; one of them is the malfunction of ion channels, resulting from mutations. Voltage-gated sodium channels (NaV) play an essential role in the generation and propagation of action potential, and malfunction caused by mutations can induce irregular neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 354 publications
(343 reference statements)
1
67
0
1
Order By: Relevance
“…The dysfunction of ion-channels (channelopathy) is known not only for AE [ 109 , 110 ], but for epilepsy and neuromuscular pathology in general [ 111 , 112 , 113 , 114 ]. Thus the membrane-potential disturbances look like the most crucial proximate cause of AE and other seizure states.…”
Section: The General Comparison Of Normal and Pathological Reactions In Ae Modelsmentioning
confidence: 99%
“…The dysfunction of ion-channels (channelopathy) is known not only for AE [ 109 , 110 ], but for epilepsy and neuromuscular pathology in general [ 111 , 112 , 113 , 114 ]. Thus the membrane-potential disturbances look like the most crucial proximate cause of AE and other seizure states.…”
Section: The General Comparison Of Normal and Pathological Reactions In Ae Modelsmentioning
confidence: 99%
“…Voltage-gated sodium channels (NaV) mainly exist in the central nervous system (CNS), Peripheral nervous system (PNS), skeletal muscle, and cardiac muscle, which are responsible for the initiation and propagation of action potentials in excitable cells. Among the nine different α subtypes of NAV (Nav1.1-Nav1.9) that have been studied, SCN1A(Nav1.1), SCN2A(Nav1.2), SCN3A(Nav1.3), SCN8A(Nav1.6), and SCN9A(Nav1.7) are gene mutations associated with channel lesions that ultimately lead to epilepsy [11,12]. SCN1A gene codes for the α subunit of the Nav1.1 sodium channel are expressed widely in CNS to inhibit GABAergic interneurons and control neuronal excitability.…”
Section: Mutation Of Sodium Channelmentioning
confidence: 99%
“…FHM is not the only family of diseases with known ion channel mutations that affect cortical excitation. Monogenic diseases related to mutations in voltage-gated sodium channels are well documented in patients with epileptic phenotypes (Menezes et al, 2020;Poulin & Chahine, 2021), including almost 2,000 identified mutations that affect sodium channel isoforms highly expressed in brain tissues (including NaV1.1, NaV1.2, NaV1.3 and NaV1.6; (Huang et al, 2017)). One of these mutations (NaV1.1) has also been identified in FHM-3 patients (Tiwari et al, 2020), although its role in migraines and CSD is less clear.…”
Section: Blockmentioning
confidence: 99%